2015
DOI: 10.5664/jcsm.5024
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Duration of Sleep and Hypertension in Adults: A Meta-Analysis

Abstract: Excessively longer and shorter periods of sleep may both be risk factors for high blood pressure; these associations are stronger in women than men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
123
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(141 citation statements)
references
References 72 publications
11
123
1
6
Order By: Relevance
“…Sleep deprivation among women (≤5 hours versus 7 hours/night) is associated with a greater risk of hypertension (odds ratio: 1.68, 95% confidence interval, 1.39–2.03) than that observed among men (odds ratio: 1.30; 95% confidence interval, 0.93–1.83); however, only 3 out of 23 reviewed studies presented findings stratified by sex 16, 17, 18, 19. Prolonged sleep onset latency increases the odds of hypertension by 300% (odds ratio: 3.27; 95% confidence interval, 1.20–8.96) 20.…”
Section: Introductionmentioning
confidence: 93%
“…Sleep deprivation among women (≤5 hours versus 7 hours/night) is associated with a greater risk of hypertension (odds ratio: 1.68, 95% confidence interval, 1.39–2.03) than that observed among men (odds ratio: 1.30; 95% confidence interval, 0.93–1.83); however, only 3 out of 23 reviewed studies presented findings stratified by sex 16, 17, 18, 19. Prolonged sleep onset latency increases the odds of hypertension by 300% (odds ratio: 3.27; 95% confidence interval, 1.20–8.96) 20.…”
Section: Introductionmentioning
confidence: 93%
“…90 Recent experiments indicate that a simulated work week with restricted sleep leads to a reduction in insulin sensitivity when early breakfasts are eaten or when timing is shifted. 84 91 Recent meta-analyses including 24 and 13 studies, 92 93 and a systematic review, 94 show that short sleep duration is related to a higher prevalence of hypertension. Some support exists for links between shift work, elevated blood pressure, hypertension, worse blood lipid profile, and blood coagulation, 6 71 as well as for blood lipids being worse in people eating more at night.…”
Section: Behavioural Mechanismsmentioning
confidence: 99%
“…Three recent systematic reviews and meta-analyses of cross-sectional and prospective epidemiologic studies have reported 20%-61% higher hypertension risk with short sleep duration. [16][17][18] In a meta-analysis by Wang et al, 18 However only 3 of the reviewed prospective cohort studies presented findings stratified by sex. [19][20][21] An analysis within the London-based Whitehall II study of 10,308 white-collar British civil servants ages 35-55 years exam-ined both the cross-sectional and prospective associations of sleep duration with prevalent and incident hypertension.…”
Section: Sleep and Cardiometabolic Risk Factorsmentioning
confidence: 99%